Photophysical and optical properties of 5-Bromo-2-nitropyridine organic molecule: Experiment and theory - Gündüz, Bayram; Kurban M. (Elsevier B.V., 2018)
The changes in the structural, electronic, vibrational and optical properties of 5-Bromo-2-nitropyridine organic molecule have been investigated. The semi-emprical realtions have been proposed for the calculation of the refractive index (n). The energy gap (Eg), harmonic frequencies, Mullkien atomic charges, density of states (DOS), radial distribution functions (RDFs) and coordination number of binary interactions were searched. Ultraviolet–visible (UV–Vis) spectral analysis has been carried out using experimental techniques and time-dependent (TD) DFT calculations. The stability of the organic compound changes based on solvent environment. Eg decreases depending on increase in the concentration. The compound in chloroform is more stable than that of the other solvents. The theoretical calculations are consistent with the experimental results. © 2018 Elsevier B.V.
Keywords: Density-functional theory; Electronic structure; Organic molecules; Photophysical properties; Refractive index